Carbon K-edge x-ray emission spectroscopy of gas phase ethylenic molecules. (16th February 2022) - Ingle, R A; Banerjee, A; Bacellar, C; Barillot, T R; Longetti, L; Coreno, M; de Simone, M; Zuccaro, F; Poletto, L; Miotti, P; Röder, A; Stolow, A; et al.
Abstract: We report on the C K-edge x-ray absorption spectra and the resonant (RXES) and non-resonant (NXES) x-ray emission spectra of ethylene, allene and butadiene in the gas phase. The RXES and NXES show clear differences for the different molecules. Overall both types of spectra are more structured for ethylene and allene, than for butadiene. Using density functional theory–restricted open shell configuration interaction single calculations, we simulate the spectra with remarkable agreement with the experiment. We identify the spectral features as being due to transitions involving localised 1s orbitals. For allene, there are distinct spectral bands that reflect transitions predominantly from either the central or terminal carbon atoms. These results are discussed in the context of ultrafast x-ray studies aimed at detecting the passage through conical intersections in polyatomic molecules.